The moderating effects of attitude on the relationship between social networking sites factors and COVID-19 vaccine acceptance in Melaka Tengah / Hanita Hassan - Hassan, Hanita (2023)
The unprecedented COVID-19 pandemic has devastated the economic and social sectors globally. Vaccines are the most effective way to overcome the crisis. However, the acceptance of vaccination is a major obstacle. Clinical tests conducted in a short and limited time frame have raised concerns about the product's validity. Previous research has shown the significance of attitudes towards vaccination behaviours. Furthermore, the effect of utilising social networking sites on people’s attitudes and behaviours is either overlooked or less examined. This study aims to determine the moderating effects of attitude on the relationship between social networking site factors of perceived usefulness, perceived ease of use, perceived religiosity, amount of information, and social affiliation and COVID-19 vaccine acceptance in Melaka Tengah. A purposive sampling method is employed in an online, cross-sectional study with a self-administered questionnaire to 411 social networking site users, aged 18 and older, who are vaccinated and knowledgeable about the COVID-19 vaccine. The data was analysed using the Statistical Package for Social Sciences (SPSS) version 26 and Hayes Process Macro version 4.1. This study uses the technology acceptance model, the tri-component model (ABC model), and the health belief model as foundational theories for conceptual framework development.